Capital Structure Determinants of Firms at Bursa Malaysia - Hadi, Abdul Razak Abdul; Rehan, Raja; Zafar, Sehrish; Khattak, Mudeer Ahmed (International Journal of Engineering and Technology, 2018)
This paper attempts to investigate the effect of total assets, fixed assets, current assets, sales, return on equity and earning per share (firmâ€™s specific factors) on capital structure of listed firms at Bursa Malaysia. The Modigliani-Miller Theory, Trade-off Theory and Pecking Order Theory are put into test in this study.Â The study is comprehensive indeed as it covers all sectors in Bursa Malaysia (both financial and non-financial sectors). The investigation is carried out on 558 listed firms from all sectors of Bursa Malaysia main market over an observed period of twelve years from 2005 to 2016. The methodology is based on static panel data model. Pooled OLS is applied to provide the base-line analysis. Debt Equity ratio is taken as a dependent variable, representing the firmâ€™s capital structure. The empirical results show that total assets, current assets, sales and earnings per share are relevant in explaining firmâ€™s capital structure.Â